Contribuições para compreensão do comportamento da base imprimada de pavimentos rodoviários - Almeida, Fernando Dácio de (2024)
Currently, there is an effort in Brazil to modernize the method of dimensioning asphalt pavements. However, it is generally observed that the consideration of the interface between the asphalt surfacing and the base layer in the pavement is not well defined, with some methods considering them perfectly bonded and others completely sliding, which can overestimate or underestimate the service life of a pavement. Given this, this research sought to clarify the behavior of the interface between the surfacing and the base, especially with regard to the adhesion between these layers provided by the bituminous prime coat, bringing more information about the behavior of this bond. Six different priming binders were investigated, in which parameters and properties such as application rate, cohesion, adhesion, wear, and volatile emissions were evaluated. From this evaluation, one of these binders (G8) was chosen to be used in the direct shear tests of the interface between the surfacing and the primed base, and from the results obtained, it was possible to perceive the effect of the priming in the form of a partial adhesion condition but approaching. Furthermore, as a way to contribute to the technical community, parameters and limits were proposed for the acceptance of the priming service, generating an advisory material in the form of a manual of practices and procedures that guide the execution, acceptance and technological control of the materials and services of bituminous priming of highways. Thus, it was also possible to infer the contribution of the priming to the adhesion and behavior of the structure from the use of two types of surfacing, in which samples with Asphalt Concrete (AC) and others with Cape Seal were used. To this end, laboratory and field parameters were generated that will contribute to the more appropriate use of the new Brazilian method of dimensioning asphalt pavements through a better understanding of the behavior of the interface between primed bases and surfacings, in order to reduce the occurrence of failures caused by asphalt priming on highways.